A strategic decision model for evaluating college and university sustainability investments. Issue 1 (14th January 2014) - Murphy, Tom; O'Brien, Will
Abstract : Purpose: – The paper aims to examine a strategic decision model and its potential value for assisting academic institutional leaders in addressing climate change by making better informed sustainability investment decisions. Design/methodology/approach: – Although the vast majority of engagements have focused on IT project selection and prioritization, it will be demonstrated that there is direct applicability to capital investment decisions related to sustainability. Examples of the results are provided with instructions on how to implement a similar approach for organizations challenged with selection and prioritization of sustainability projects. Finally, the model is assessed critically in terms of challenges and lessons learned from client projects. Findings: – The strategic decision model has been found to provide a broader framework for decisions, i.e. both qualitative and quantitative. At the same time, the methodology used with the model engages more stakeholders in the process to help build consensus regarding investment and project decisions. As a portfolio-based model, relative value and risk can be viewed easily to enable focus on what the stakeholders believe to be key projects. This perspective and the functionality of the application enable action to be taken by the decision maker to possibly reduce project risk and/or increase potential value of specific projects. Research limitations/implications: – It was determined that additional research, data collection and application development would be necessary if the model were to be used for benchmarking for sustainability planning investment decisions. Practical implications: – The paper proposes that colleges and universities consider the use of the portfolio decision model and, where appropriate, implement the model as part of their sustainability program. The anticipated benefits of this action would include: greater involvement of key stakeholders in support of required organizational change, improvement in the quality of investment decisions, increased success of sustainability projects and data which will enable future benchmarking. Originality/value: – Given this emergent leading role of universities in championing sustainability efforts, the purpose of this paper is to provide college and university leaders a tool to address the challenges related to investment decisions targeted at sustainability projects, such as environmental footprint reduction in support of achieving sustainability for their respective institutions.